2014
DOI: 10.1007/s40097-014-0091-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamic insight into the ethanol effect on Tretinoin drug delivery through carbon nanotubes

Abstract: Carbon nanotubes as potential material for drug delivery can pass through cell walls, transfer, and liberate drugs in particular tissues. The goal of this article is to survey the insertion of an anticancer drug called Tretinoin into CNT (10, 7) and CNT (8, 5). All computations are surveyed by molecular dynamics simulation in various temperatures (270 and 310 K) and in water solution and ethanol co-solvent. 0.2 M ethanol is studied that is more than normal range of blood alcohol content. The molecular dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 28 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…In MD simulations the effect of the ethanol (EtOH) as a co-solvent in different concentrations (1, 0.5 and 0.1 M) have been investigated. EtOH is considered as a model to explore the balance of hydrophobic interactions and H-bonds in the biological systems [322]. DFT calculation showed that the negative values of the E ads and solvation energies (E sol ), the difference between the energy obtained in solution and the energy obtained in gas, demonstrate that all studied configurations are stable.…”
Section: Other Cytostaticsmentioning
confidence: 99%
“…In MD simulations the effect of the ethanol (EtOH) as a co-solvent in different concentrations (1, 0.5 and 0.1 M) have been investigated. EtOH is considered as a model to explore the balance of hydrophobic interactions and H-bonds in the biological systems [322]. DFT calculation showed that the negative values of the E ads and solvation energies (E sol ), the difference between the energy obtained in solution and the energy obtained in gas, demonstrate that all studied configurations are stable.…”
Section: Other Cytostaticsmentioning
confidence: 99%